Acceptance of the Madrasati (M) LMS among public school teachers as affected by behavioral intention in Riyadh - Alharbi, Hamad Muaybid; Ab Jalil, Habibah; Omar, Muhd Khaizer; Mohd Puad, Mohd Hazwan (Little Lion Scientific, 2022)
The utilisation of Madrasati (M) LMS among school teachers has become crucial in teaching and learning in Saudi Arabia, specifically in Riyadh. However, the acceptance and utilisation of the M LMS are still poor in KSA. Teachers' acceptance and use of M LMS are linked to the Unified Theory of Acceptance and Use of Technology (UTAUT) and Technology Acceptance Model (TAM) factors. This study aims to determine whether performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), attitude, and competence to use M significantly influence behavioral intention (BI) to utilise M among teachers in Saudi public schools in Riyadh. Consistent with this objective, the quantitative research design, specifically the survey technique, was used to collect data from a sample of 374 public school teachers in Riyadh. The results revealed that UTAUT (PE, EE, SI, FC) and TAM (competence) factors significantly affected M LMS utilisation among teachers, while attitude had no significant effect on M LMS utilisation. The study found that out of six tested hypotheses, H1, H2, H3, H4, and H6 were accepted, while H5 was rejected. It can be concluded that PE, EE, SI, FC, and competence significantly affect M LMS utilisation among teachers in Riyadh.